Novel family members of CYP109 from Sorangium cellulosum So ce56 exhibit characteristic biochemical and biophysical properties. (17th February 2013) - Khatri, Yogan; Hannemann, Frank; Girhard, Marco; Kappl, Reinhard; Même, Aurélie; Ringle, Michael; Janocha, Simon; Leize‐Wagner, Emmanuelle; Urlacher, Vlada B.; Bernhardt, Rita; Gilardi, Gianfranco
Abstract The members of the CYP109 family (CYP109C1, CYP109C2, and CYP109D1) from Sorangium cellulosum So ce56 are among the 21 P450 enzymes, of which only CYP109D1 and CYP264B1 have so far been functionally characterized. Here, we attempted to characterize two other P450s (CYP109C1 and CYP109C2) for the first time and compare their biochemical, biophysical, and functional properties to those of the fatty acid hydroxylating CYP109D1. Considering the physiological importance of fatty acids, we investigated saturated fatty acid binding and conversion for all members of the CYP109 family. The interaction between the CYP109 members and different autologous/heterologous redox partners was compared using Biacore measurements in which only CYP109D1 and bovine adrenodoxin (Adx) formed a complex. Surprisingly, this interaction was similarly efficient as the interaction of Adx with its mammalian redox partners. The in vitro reconstitution assays showed no activity when using CYP109C1, although substrate binding was demonstrated; also, there was subterminal hydroxylation of saturated fatty acids, when using CYP109C2 and CYP109D1, where CYP109D1 was a much more efficient fatty acid hydroxylase. Interestingly, the hydroxylation position moved inside the fatty acid chain when using long‐chain fatty acids, thus producing possible precursors for physiologically important products.